Persistence of neutralizing antibodies a year after SARS‐CoV‐2 infection in humans - Haveri, Anu; Ekström, Nina; Solastie, Anna; Virta, Camilla; Österlund, Pamela; Isosaari, Elina; Nohynek, Hanna; Palmu, Arto A; Melin, Merit (European journal of immunology, 2021)
Most subjects develop antibodies to SARS‐CoV‐2 following infection. In order to estimate the duration of immunity induced by SARS‐CoV‐2 it is important to understand for how long antibodies persist after infection in humans. Here, we assessed the persistence of serum antibodies following WT SARS‐CoV‐2 infection at 8 and 13 months after diagnosis in 367 individuals. The SARS‐CoV‐2 spike IgG (S‐IgG) and nucleoprotein IgG (N‐IgG) concentrations and the proportion of subjects with neutralizing antibodies (NAb) were assessed. Moreover, the NAb titers among a smaller subset of participants (n = 78) against a WT virus (B) and variants of concern (VOCs): Alpha (B.1.1.7), Beta (B.1.351), and Delta (B.1.617.2) were determined. We found that NAb against the WT virus persisted in 89% and S‐IgG in 97% of subjects for at least 13 months after infection. Only 36% had N‐IgG by 13 months. The mean S‐IgG concentrations declined from 8 to 13 months by less than one third; N‐IgG concentrations declined by two‐thirds. Subjects with severe infection had markedly higher IgG and NAb levels and are expected to remain seropositive for longer. Significantly lower NAb titers against the variants compared to the WT virus, especially after a mild disease, suggests reduced protection against VOCs. A year after WT SARS‐CoV‐2 infection high seropositivity rate was observed: 89% of subjects had persisting neutralizing antibodies and up to 97% had anti‐spike IgG antibodies. Compared to the WT virus, neutralizing antibody titers were reduced for variants of concern Alpha, Beta, and Delta.